High Yield to 1-Propanol from Crude Glycerol Using Two Reaction Steps with Ni Catalysts - Gatti, Martín Nicolás (2020)
The objective of the present work is to achieve high yield to 1-propanol (1-POH) by crude glycerol hydrogenolysis in liquid phase and find an alternative to the use of noble metals by employing Ni catalysts. Two Ni catalysts with different supports, alumina ( -Al2O3), and a phosphorous-impregnated carbon composite (CS-P) were studied and characterized in order to determine their acid properties and metallic phases. With the Ni/ -Al2O3 catalyst, which presented small particles of metallic Ni interacting with the acid sites of the support, it was possible to obtain a complete conversion of crude glycerol with high selectivity towards 1,2-propylene glycol (1,2 PG) (87%) at 220 °C whereas with the Ni/CS-P catalyst, the presence of AlPOx species and the Ni2P metallic phase supplied acidity to the catalyst, which promoted the C-O bond cleavage reaction of the secondary carbon of 1,2 PG to obtain 1-POH with very high selectivity (71%) at 260 °C. It was found that the employment of two consecutive reaction stages (first with Ni/ -Al2O3 at 220 °C and then with Ni/CS-P at 260 °C) allows reaching levels of selectivity and a yield to 1-POH (79%) comparable to noble metal-based catalysts.